Effect of precursors on β-alumina electrolyte preparation. Issue 7 (July 2015) - Barison, S.; Fasolin, S.; Mortalò, C.; Boldrini, S.; Fabrizio, M.
Abstract: This work describes the synthesis of Mg 2+ - and Li + -stabilized β-alumina solid electrolytes (Na1.67 Mg0.67 Al10.33 O17 and Na1.67 Li0.33 Al10.67 O17 respectively) and investigates the influence of different Al2 O3 precursors and stabilizers on their structural properties. The β-alumina precursors were α-Al2 O3, γ-Al2 O3, Pseudo-Boehmite (AlOOH·H2 O) and Bayerite (Al(OH)3 ), with Na2 CO3 as sodium source and MgCO3 or LiCO3 as phase stabilizers. The effect of composition and processing on phase purity and microstructure of sintered specimens was inspected by X-ray diffraction, simultaneous thermal gravimetry – differential scanning calorimetry coupled with residual gas analysis and scanning electron microscopy. Linear shrinkage evaluation was carried out by dilatometry. Furthermore, the influence of composition, structure and density on electrical properties was also investigated finding conductivity values up to 0.14 Ω −1 cm −1 at 300 °C for Li + -stabilized β-alumina.